Re-Design Strategi of PT Semen Tonasa Menggunakan Analisis SWOT dan QSPM Paska Penarikan Fungsi Marketing Ke Holding PT. Semen Indonesia (Persero) Tbk - Anis -; Abdul Rahman Laba; Erlina Pakki (Hasanuddin Journal of Business Strategy, 2019)
The purpose of this study was to find out and analyze the strategy re-design at PT Semen Tonasa using SWOT analysis and QSPM after the withdrawal of marketing functions to the holding company PT. Semen Indonesia (Persero) Tbk. To apply these objectives, data collection techniques are used through interviews, literature studies, and documentation, with EFE matrix data analysis techniques, IFE, CPM, and QSPM matrices. The results of the analysis conducted found that the SWOT analysis in the Re-design strategy at PT. Semen Tonasa, Tbk. after the withdrawal of the marketing function to the holding PT. Semen Indonesia, Tbk. which indicates that the company PT. Semen Tonasa, Tbk. has great strength and opportunity, so the company can overcome the weaknesses and threats faced when running the cement industry. From the results of the analysis through the Space matrix, IE shows that the strategy that is suitable to use is an aggressive growth strategy. Based on the results of the QSPM analysis in determining the strategy at PT. Semen Tonasa after the withdrawal of the marketing function to the holding PT. Semen Indonesia, Tbk. it can be said that an aggressive strategic alternative that is suitable for use is through product development which can include: a) Paying attention to the quality of existing cement products so that they can compete more with other cement industry companies, b) empower HR who compete in the field of work that done so far, c) Training in order to increase knowledge, skills, skills in the field of work carried out so far, d) Expand the cement distribution network in each region through the availability of transportation ports for the distribution of finished goods both in the region and in outside Sulawesi, e) Expanding market share by selling products and services to existing customers, f) expanding cement production to new areas, and g) creating new target markets and customers.